Promising antitumor therapeutics of herbal origin: exploring cytotoxic activity of glycoalkaloids and unraveling underlying mechanisms. - Farrag, Noha Nagdy (AUC Knowledge Fountain, 2015)
To evaluate the anticancer potential of the extracts of the two Solanaceae family plants: Solanum macrocarpon (African Eggplant) and Solanum seaforthianum (Brazilian Nightshade), cytotoxicity screening was performed. The extract exhibiting the most potent effect; Total glycoalkaloid extract of Solanum seaforthianum (TGASS) was then investigated further, through screening of individual compounds fractionated from it and comparing their cytotoxicity with each other and with other standard Solanum alkaloids. Further investigations were performed to define the underlying mechanisms by which each of the three most potent alkaloids function on hepatocellular carcinoma (HepG2) cell line. The hypothesis involves that alkaloids fractionated from the Solanaceae family of plants posses a promising antitumor activity. The two main aims were to: i) Determine the most potent compounds through cytotoxicity screening Sulforhodamine B (SRB) assay on both of HepG2 and urinary bladder cancer (SCaBER) cell lines. ii) Explore the molecular mechanisms by which these compounds exert their cytotoxic effect. The most potent alkaloids: (Solanine, Solamargine and Nitroso-Solamargine) were investigated further, by estimation of cell cycle induced alterations via flowcytometry. Expression of cyclin D1 was then evaluated by immunocytochemistry. Ki67, survivin, caspase-3, caspase-9 gene expression was evaluated through quantitative Reverse Transcription Polymerase Chain Reaction (qRT-PCR). B cell lymphoma 2-associated X (Bax) protein expression was evaluated by western blot. Caspase-3, caspase-9, Bax and B cell lymphoma-2 (Bcl-2) protein expression were estimated using ELISA (Enzyme- Linked Immunosorbent Assay). On HepG2: the three alkaloids produced an increase in the Pre-G phase, a reduction in the proliferation phases: S-phase and G2/M phase and a reduction in the G0/G1 phase. Nitroso-Solamargine has produced the greatest reduction in the S-phase and the highest increase in the Pre-G. CyclinD1 was reduced only with Solamargine and Nitroso- Solamargine; Ki67 and survivin were reduced by the three alkaloids. Nitroso- Solamargine exhibited the highest reduction. Bax, caspase-3 and caspase-9 were upregulated, with Nitroso-Solamargine exhibiting the highest upregulation, whereas Bcl- 2 was a little upregulated opposite to what is anticipated. In conclusion, The three glycoalkaloids: Solanine, Solamargine and Nitroso-Solamargine has exhibited the lowest IC50 values on both of HepG2 and SCaBER cell lines, with Nitroso-Solamargine exhibiting the lowest IC50 values as well as the most prominent upregulation of intrinsic apoptotic markers and downregulation of proliferation markers, indicating an important role of the Nitroso moiety in enhancing the cytotoxic activity of Solamargine.